Multi-colorized tint map for distinguishing triple-negative breast cancers from cysts and fibroadenomas based on the tumor margin - Xiang, Hongjin; Chen, Xiaoyu; Tan, Xiao; Chen, Xiangmei; Lv, Heng; Sun, Desheng (Frontiers in Oncology, 2026)
BackgroundTriple-negative breast cancer (TNBC) can appear markedly hypoechoic on grayscale ultrasound and may mimic benign entities such as cysts and fibroadenomas, complicating preoperative differentiation. Because the human visual system is more sensitive to multi-color patterns than to subtle grayscale contrast, we investigated whether hue, saturation, and value (HSV)-based multi-colorized tint maps could improve visual discrimination of TNBC from benign, extremely hypoechoic breast lesions.MethodsThis single-center retrospective study included 48 histopathologically confirmed, extremely hypoechoic lesions (16 TNBCs, 16 cysts, and 16 fibroadenomas). Grayscale ultrasound images were post-processed into HSV tint maps using two pre-specified color-coding strategies. A single intensity threshold (135) was predefined and then fixed across all cases to enhance reproducibility; its stability was examined in sensitivity analyses around the selected value. Two radiologists independently reviewed grayscale and colorized images in separate, blinded sessions with randomized case order and a washout interval between sessions to reduce recall bias. Diagnostic performance and inter-reader agreement (Cohen’s κ) were assessed.ResultsMulti-colorized tint maps enhanced subtle marginal echogenic transitions. TNBC more frequently exhibited a distinctive peripheral “halo” pattern, whereas this feature was uncommon in cysts and fibroadenomas. For differentiating TNBC from benign lesions, sensitivity/specificity improved from 75%/69% on grayscale to 88%/91% with multi-colorization. Inter-reader agreement for the colorized interpretation was high (κ =0.88).ConclusionHSV-based multi-colorized tint maps reveal a visually intuitive marginal “halo” feature that may assist preoperative differentiation of TNBC from benign, extremely hypoechoic lesions and can improve diagnostic performance compared with grayscale ultrasound. Future multicenter studies should validate robustness across ultrasound vendors and prospectively correlate the halo with histopathologic characteristics (e.g., cellularity and stromal response).